2013
DOI: 10.1097/mib.0b013e3182802ab6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Ulcerative Colitis in Koreans Suggests Extensive Overlapping of Genetic Susceptibility With Caucasians

Abstract: Our data support the biologic significance of the overlapping loci for UC between Caucasian and Korean populations. Our data suggest that genetic associations for UC tend to overlap more extensively among different ethnic groups than those for Crohn's disease, which shows well-established dependence on ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 41 publications
3
41
0
1
Order By: Relevance
“…10 The non-European UC GWAS performed to date also identified novel susceptibility loci 11 and revealed shared UC risk loci between European and non-European cohorts. 12 These UC-specific studies also confirmed the longestablished association between UC and the classical human leukocyte antigen (HLA) locus, which contains genes encoding antigenpresenting proteins, and plays a crucial role in the regulation of the adaptive immune system.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…10 The non-European UC GWAS performed to date also identified novel susceptibility loci 11 and revealed shared UC risk loci between European and non-European cohorts. 12 These UC-specific studies also confirmed the longestablished association between UC and the classical human leukocyte antigen (HLA) locus, which contains genes encoding antigenpresenting proteins, and plays a crucial role in the regulation of the adaptive immune system.…”
Section: Introductionmentioning
confidence: 54%
“…13 However, neither CFB nor SLC44A4 have been identified in any of the larger Caucasian GWAS, [3][4][5][6][7] their meta-analysis 8,9 and more recently in ImmunoChip analysis, 10 or in the non-European UC cohorts studied to date. 11,12 Needless to say, such a striking difference across ethnic groups may be due to inherent statistical limitations of GWAS, which mainly relies on single SNP analysis, incomplete coverage of functional common or rare variants, poor representation of appropriate proxies on commercial genotyping arrays due to population-specific LD patterns, among others factors like allelic/genetic heterogeneity, varying environmental components like gut microbiome influenced by geographical location, lifestyle factors such as diet, smoking, etc. leaving much of the disease heritability unexplained.…”
Section: In Silico Analysis Of Slc44a4 Snpsmentioning
confidence: 99%
“…Meta-analysis of the GWAS identified 163 risk loci for IBD [4]. GWAS of IBD in Asia have been reported in Japan, Korea and India [24,25,26,27,28,29,30]. The loci identified in Asian studies are listed in table 2.…”
Section: Ibd Genetic Studies In Asiamentioning
confidence: 99%
“…We combined data from 915 individuals with IBD [CD, 532; UC, 383] and 745 healthy controls included in our previously published GWAS, 29,31 with additional data of 590 individuals with IBD [CD, 390; UC, 200] and 3296 population controls from the Korea National Institute of Health, to increase the power of our GWAS-based discovery analysis. 27 The …”
Section: Study Populationmentioning
confidence: 99%
“…In our previously published GWAS, 29,31 IBD cases were genotyped using Illumina OmniExpress arrays; newly included IBD cases were genotyped using Illumina OmniExpressExome arrays. 27 All controls were genotyped using Illumina Omni1-Quad arrays.…”
Section: Genotyping and Quality Controlmentioning
confidence: 99%